Quality Analysis Of Fruit Leather From Mixed Fruit Of Pedada (Sonneratia Caesolaris) And Mango Fruit - syaedah, Nur; Faridah, Anni (Universitas Negeri Padang, 2023)
Fruit leather is a snack made from fruit puree in the form of thin sheets, plastic texture and can be rolled up. Pedada fruit is a type of mangrove fruit that is rarely used by the community because of its sour taste, so it needs to be combined with fruit that has a sweet taste, such as mango. The purpose of this study was to obtain the best quality fruit leather from a combination of pedada fruit (Sonneratia caseolaris) and mango fruit. This type of research was a pure experiment using a completely randomized design (CRD) with four treatments and three repetitions. The treatment given to the ratio of broiler and mango fruit in the manufacture of fruit leather is X1(1:0 / 100:0), X2(3:1/ 75:25), X3(1:1/ 50:50) and X4(1:3/ 25:75). Data were obtained from five limited panelists who had carried out organoleptic tests. Data will be analyzed statistically using Analysis of Variance (ANOVA). If the analysis of variance shows Fcount>Ftable then Duncan's test will be continued. The results showed that there was a significant effect between X1, X2, X3 and X4 on the quality of shape, color and taste of the fruit leather and there was no significant effect on the quality of the aroma and texture of the fruit leather. The best fruit leather quality test results were obtained at 1:1 treatment with a balanced composition of 50:50.